Pengaruh Viral Marketing, Endorsement, Dan Brand Ambassador Terhadap Keputusan Pembelian Pada Parfum Geamoore Malang (Studi Kasus Pada Warga Kota Malang) - Maharani, Sonia; Salim, Muhammad Agus; Slamet, Afi Rachmat (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research was conducted to determine and analyze the influence of viral marketing, endorsements, and brand ambassadors on purchasing decisions. The population in this study are city residents who use Geamoore perfume and the exact population size is not yet known. The approach method uses a non-probability sampling technique, namely purposive sampling, namely a sample collection technique based on certain criteria using a questionnaire distributed to 95 respondents and using the SPSS analysis tool. The research results show that viral marketing, endorsements, and brand ambassadors simultaneously and partially influence purchasing decisions. Keywords: Viral marketing, endorsement, brand ambassador, purchasing decisions